A fourth algebraic order explicit trigonometrically- fitted modified Runge-Kutta method for the numerical solution of periodic IVPs - Alshareeda, Firas Adel Fawzi; Senu, Norazak; Ismail, Fudziah; Abdul Majid, Zanariah (Indian Society for Education and Environment, 2016)
This study has constructed an explicit Trigonometrically-Fitted Modified Runge-Kutta (TFMRK) method for solving first-order differential equations with periodic solutions. The newly developed method was made according to the method of Runge-Kutta Dorm and to fourth algebraic order. Numerical results for the new method were compared with the existing method, showing the potential of the new method over other existing methods.